PENGARUH KAFEIN TERHADAP BERBAGAI PARAMETER AKTIVITAS FISIK DAN METABOLIK PADA POPULASI SEDENTER SEBAGAI UPAYA MENURUNKAN RISIKO PENYAKIT KARDIOVASKULAR: SEBUAH KAJIAN SISTEMATIS - Valerie Josephine Dirjayanto (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Current circumstances regarding the development of cardiovascular disease in Indonesia is causing remarkable concerns as its metabolic risk factors become more uncontrollable. As a way to prevent cardiovascular disease, physical activity must be done adequately and efficiently, especially in sedentary individuals, to improve metabolic profile. This review is aimed to assess the effect of caffeine to various physical activity and metabolic parameters in sedentary individuals. Methods: A systematic review was conducted through PubMed, Cochrane, EBSCOhost, and Scopus, in search for clinical trials implementing caffeine together with physical activity in sedentary individuals and its efficacy in prevention, thus correlating it with cardiovascular risk factors. Quality assessments of studies selected were performed with Revised Cochrane risk of bias tool for randomized trials (RoB 2.0). Discussion: The search yielded 5 clinical trials with a total of 90 subjects. Caffeine in addition to physical activity is proven effective in controlling various metabolic parameters in sedentary subjects. The intervention elicits more efficient weight loss, induces more energy consumption, improvement in VO2max, and increases oxygen consumption. Caffeine also improves lipid profile as well as blood pressure. No significant adverse effects are reported. Conclusion: Caffeine showed promising potentials in increasing the effectiveness of physical activity in controlling metabolic profile and eventually lower the risk for cardiovascular diseases in sedentary individuals. Further studies with larger samples are required in order to substantiate the evidence.